Effect of different starter cultures on the control of biogenic amines and quality change of douchi by rapid fermentation. (July 2019) - Tan, Yue; Zhang, Renfeng; Chen, Guangjing; Wang, Shasha; Li, Changfeng; Xu, Yao; Kan, Jianquan
Abstract: Naturally fermented douchi always yields large amounts of biogenic amines (BAs). To improve the safety and quality of douchi and shorten its fermentation cycle, investigations were carried out using six selected microbial strains, including Aspergillus oryzae 2339 (Shanghai brewing 3.042), A. oryzae 41380, A. oryzae 40188, Mucor racemosus, Actinomucor elegans, and M. wutungqiao for douchi rapid fermentation. Results showed that the water content, pH, free amino-type nitrogen, and titratable acidity of all samples were at normal levels for mature douchi products. All six types of douchi obtained ornithine decarboxylase and tyrosine decarboxylase. Only putrescine and spermidine were detected in the final douchi products. The contents of total BAs were at low and safe levels, ranging from 22.47 mg/kg to 40.95 mg/kg. These findings demonstrated that the selected strains were suitable for producing douchi products with good quality and low levels of BAs through rapid fermentation. Highlights: Rapid fermentation with pure starter culture was adopted for douchi production. The selected strains were effective for reduction of biogenic amines. Actinomucor elegan was suitable for douchi rapid fermentation production.